Design And Characterization Of Silicon Nanowire Transistor And Logic Nanowire Inverter Circuits - Naif, Yasir Hashim (2013)
The most important limitation in planer MOSFETs is current leakage between the source and the drain at the off-state (IOFF), which presents a critical problem in securing circuit reliability. To mitigate this problem, there are new types of transistors with a 3D structure, including silicon nanowire transistors (SiNWT). In order to optimize dimensions, ambient temperature and orientation of channel in SiNWT design, simulation is needed to characterize the behaviour of the SiNWT and help making design decisions. Over the last decade, there have been many researches focused on SiNWTs fabrication fields. However, these researches are all based on fabrication fields. Therefore, in this research, dimensions, ambient temperature and orientation of channel are modelled and taken into account to analyze performance improvement of SiNWT. Furthermore, in order to optimize dimensions, and logiclevel voltages of nanowire logic inverters circuits design, simulation is needed to characterize the limits of noise margins of the NW logic inverter and help making design decisions. There have been some proposed researches focused on NW logic inverters fabrication without focusing on optimization of logic levels and dimensions depending on noise margins as a limitation factor which represents a critical factor in the working of logic circuits performance, and this study is intended to be the first research to demonstrate dimensional optimization of nanowire logic inverter. This research contains two main parts, first part on the characterization of silicon nanowire transistor and the second on studying the characteristics of nanowire (NW) inverters.